Economic advantages of community currencies - Sarah Zeller (Journal of Risk and Financial Management, 2020)
Community currencies are only sometimes economically advantageous. We focus on seasonal changes in money supply and assume that community currencies stabilize the money supply in a local community. This leads to additional transactions during seasons of insufficient supply of national currency. We hypothesize community currencies are therefore economically advantageous in a surrounding of seasonally insufficient money supply. We test the hypothesis qualitatively with two case studies, the German Chiemgauer and the Kenyan Sarafu Credit. We find community currencies are only economically advantageous in an environment of insufficient liquidity.
Keywords: 330; community currencies; complementary currencies; money supply; seasonal liquidity